WSDMDA: An enhanced Model Driven Web engineering methodology - Mukhtar, M.A.O. (Institute of Electrical and Electronics Engineers Inc., 2014)
Model-Driven Engineering (MDE) paradigm has been successfully adopted in many applied research environments with promising results, and applied to Web engineering area as well. Model-driven Web Engineering (MDWE) refers to the use of the model-driven engineering paradigm in Web development methodologies. It uses the models previously developed with the information obtained at the earlier stages to derive models within the current stage of the development process. Model Driven Architecture (MDA) is considered as a most important realization of MDE; therefore, it is used as a basic reference framework in this research work. One of the challenges faced by the Model-Driven Web Engineering community along the evolution of Web applications was influencing the MDA Components in all stages of web site development process. This research paper represents the enhancement process for one of existing Web Engineering (WE) approach called Web Site Design Method (WSDM) by our MDA-Based WE mechanism. The resulting method is a new MDWE methodology called MDA-based WSDM (WSDMDA). Â© 2014 IEEE.